BASIC CONCEPTS OF THE PRAGMATICS OF THE TEXT - Удовіченко, Ганна; Дмитрук, Лілія (SWorldJournal, 2022)
The article considers the study of literary text in a pragmatic aspect, which can offer interesting ways to solve the problem of interpretation of both linguistic facts and literary text in general. The authors note that the current period of development